По биквадратным уравнениям (x-2)^2(x^2-4x)+3=0

gek45 gek45    2   30.05.2019 13:50    0

Ответы
maximborisoc maximborisoc  01.10.2020 15:06
(x-2)^2(x^2-4x)+3=0
x^4-8x^3+20x^2-16x+3 = 0
(x-1) (x^3-7x^2+13x-3) =0
(x-1)(x-3) (x^2-4x+1) =0
отсюда видно
(x-1) =0 \\ x_{1} =1
и
(x-3) =0 \\ x_{2} =3
и
(x^2-4x+1) =0
решаем квадратное уравнение
x_3 = 2+\sqrt{3},\; x_4 = 2-\sqrt{3}

ответе:
x_{1} =1
x_{2} =3
x_3 = 2+\sqrt{3}
x_4 = 2-\sqrt{3}
ПОКАЗАТЬ ОТВЕТЫ
dashponi2007 dashponi2007  01.10.2020 15:06
(x-2)^2(x^2-4x)+3=0
(x^2-4x+4)(x^2-4x)+3=0
x^2-4x=t
(t+4)*t+3=0
t^2+4t+3=0
(t+1)(t+3)=0
t=-1
x^2-4x==-1
x^2-4x+1=0
x12=(4+-корень(16-4))=(-4+_корень(12))/2=-2+-корень(3)
t=-3
x^2-4x+3=0
x34=(4+-корень(16-12))/2=(4+-2)/2= 1 3
x=1 3 -2+-корень(3)
ПОКАЗАТЬ ОТВЕТЫ